2023
DOI: 10.1038/s41598-023-31869-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting prostate cancer in men with PSA levels of 4–10 ng/mL: MRI-based radiomics can help junior radiologists improve the diagnostic performance

Abstract: To develop MRI-based radiomics model for predicting prostate cancer (PCa) in men with prostate-specific antigen (PSA) levels of 4–10 ng/mL, to compare the performance of radiomics model and PI-RADS v2.1, and to further verify the predictive ability of radiomics model for lesions with different PI-RADS v2.1 score. 171 patients with PSA levels of 4–10 ng/mL were divided into training (n = 119) and testing (n = 52) groups. PI-RADS v2.1 score was assessed by two radiologists. All volumes of interest were segmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…A total of 19 studies with 3879 participants that met the inclusion criteria were chosen for the final analysis [ 16 34 ]. The authors of 10 (2205 patients) and 13 studies (2965 patients) reported the diagnostic performance of MRI for detecting csPCa [ 16 22 , 28 , 31 , 32 ] and PCa [ 18 , 19 , 23 30 , 32 34 ], respectively. The detailed research selection process is presented in the Supplemental Materials (S-2) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 19 studies with 3879 participants that met the inclusion criteria were chosen for the final analysis [ 16 34 ]. The authors of 10 (2205 patients) and 13 studies (2965 patients) reported the diagnostic performance of MRI for detecting csPCa [ 16 22 , 28 , 31 , 32 ] and PCa [ 18 , 19 , 23 30 , 32 34 ], respectively. The detailed research selection process is presented in the Supplemental Materials (S-2) .…”
Section: Resultsmentioning
confidence: 99%
“…The MRI characteristics are summarized in Table 3 . Eleven studies entailed the use of 3-T scanners [ 17 – 19 , 21 23 , 28 , 29 , 31 , 32 , 34 ], six studies used 1.5-T scanners [ 20 , 24 27 , 30 ], one study used both [ 16 ]; one article did not provide relevant explanations [ 33 ]. The relevant elements are described in detail in the Supplemental Materials (S-4) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation